Deterioration mechanism of physical and mechanical properties of phosphate rock under seismic disturbance and saturation - Li, Shujian; Wang, Hao; Wang, Chongyang; Zhang, Bin; Zhang, Dongming (Frontiers in Earth Science, 2023)
To explore the influence of seismic disturbance and saturation on the mechanical properties of phosphate rock, the paper divided phosphorus rock into natural group, water-saturated Group and ‘earthquake & water-saturated’ group. Fatigue loading and conventional triaxial compression tests were carried out to study the physical characteristics, degeneration characteristics, strength characteristics and failure characteristics of the samples. The conclusions are as follows: The average wave velocity of samples of water-saturated group and ‘earthquake & saturation’ group is 29.7% and 52.9% lower than that in natural group, respectively, and the average peak strength under various confining pressure conditions is 32.2% and 48.3% lower than that in natural group, respectively, indicating that both seismic stress loading and saturation have deterioration effects on the samples. Compared with natural group and water-saturated group, after simulated seismic stress loading, the stress-strain curve of ‘earthquake & water-saturated’ group shakes obviously after the peak, and the steps appear frequently, showing obvious plastic characteristics. Due to the different deterioration degree of the samples, the samples of the natural group were in the overall state of compression during the triaxial test, while the samples of the water-saturated group were compressed before failure and expanded after failure. The sample of‘earthquake & water-saturated group is in the whole state of expansion. The failure characteristics of natural samples and water-saturated samples are shear or shear failure. The shear plane starts from the edge of sample end face and presents typical diagonal shear failure. The failure characteristics of ‘earthquake & water-saturated’ group samples are heavy shear and through failure. There are several fracture zones extending inward from the end of the sample, resulting in obvious transverse expansion.